THE EFFECT OF PICTURE SERIES TO THE STUDENTS’ ABILITY IN WRITING NARRATIVE TEXT - Mentari Florentina Pasaribu; Riana Br Sianipar; Marintan Simbolon; Vivi Enzelia Hutabarat; Natalia Widya Pasca Tarigan (STKIP PGRI Jombang, 2020)
This article is entitled with “ The Effect of Picture Series to the Students’ Ability in Writing Narrative Text”. This research is intended to know the effect of using picture to the students’ ability in writing narrative text. In order to answer the problem, the researchers use some theories, namely: Cohen and Riel (1989), Byrne (1997), Heaton (1988), Callahan (1992). In this article, the researchers use quantitative methodology. Researchers use students at SMAS Dharma Pancasila Medan grade XI as the population and use 58 students as the sample. The instrument in this article is a written test and the test is about writing Narrative text. From the data analysis, the researchers give the score of each student in every group and calculate it, the researchers find that the result of analyzing the data, the score of t-test is higher than t-table, where the t-table is 2.00 and t-test is 7.00. So, t-test is higher than t-table. The data analysis shows that there is a significant effect in using series of picture to the ability of the students in writing narrative text at grade XI of SMAS Dharma Pancasila. It meant that Ha was accepted H0 was rejected.